Analisis Pengaruh Variasi Kecepatan Spindel Dan Feeding Terhadap Nilai Kekasaran Permukaan Proses Finishing Bubut CNC - Smith, Adam; Oktriadi, Yudi (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
In the industrial sector, technological progress has experienced very rapid development. So that the manufacturing industry is required to be able to produce quality products and a high level of accuracy with fast processing. One machine that can meet these demands is a CNC lathe, where a CNC lathe is a machine that is controlled using a computer system in its operation. In the machining process of CNC lathes, the level of surface roughness of the machining material is of great concern, because the lower the surface roughness value, the better the quality of the product. Therefore, the aim of this study was to obtain a low surface roughness value using a finishing cutting edge. The material used is AISI 1045 steel which is turned using a MORI SEIKI SL-25 CNC machine. The parameters used are spindle speed and feeding. The research method used was the Taguchi method with an orthogonal matrix L9(32) experimental design and 3 replications were carried out to reduce large deviations. The result of this research is to obtain a combination of parameters that produce minimum surface roughness values, namely spindle speed of 1804 rpm and feeding of 0.1 mm/put. And the parameter that has the greatest effect on the value of roughness is feeding with a difference of 16.029 and the one that has the least effect on the value of surface roughness is spindle speed with a difference of 1.384.